“Suddenly Afraid”: Challenged Identities and Disrupted Meaning in Lydia Davis’s Short Fiction - Mohsen Hanif; Zahra Amini (Critical Literary Studies)
Implementing Julia Kristeva’s theory of abjection, the present study attempts to demonstrate that the short fiction of Lydia Davis, contemporary American writer, is, first and foremost, about the fragility of identity and the precariousness of its borders. Using a descriptive-analytical approach and Kristeva’s Powers of Horror: An Essay on Abjection, as the main source in which she delineates her theory, this paper studies four of Lydia Davis’s short stories in depth. Abjection is the process in which the subject casts aside anything foreign to the self, or the ‘abject,’ at an early stage, to safely procure a coherent I. By detecting and interpreting two of the abject’s main manifestations, namely women and corpses, the current article will contend that Davis’s characters/narrators are always already stuck in seemingly bottomless pits of identity crises, both inside and through their use of language. Analyzing Davis’s “The Thirteenth Woman,” “Suddenly Afraid,” “Grammar Questions,” and “Letter to a Funeral Parlor,” this research tries to unravel the intricacies of maintaining shaken identities and endangered subjectivities at the face of unimaginable horror. Although discarded repeatedly by the characters in these stories, the abject never vanishes; it keeps haunting the periphery of selfhood and the solidarity of meaning.